The Objectivation of Qur'anic Values in Strengthening Students' Religious Character in Islamic Education Institutions - Arifianto, Andry; Prabowo, Galuh; Setiawan, Andi; Sain, Zohaib Hassan; Robbani, Hafidhur Rohman Saad (Maharot : Journal of Islamic Education, 2025)
The phenomenon of adolescent moral decline in the midst of globalization and digitalization poses a significant challenge for Islamic educational institutions in Indonesia, particularly tahfidz-based madrasahs. This condition demands the presence of strong Islamic leadership that not only manages administratively but also inspires and nurtures a religious culture within the school environment. This study aims to explore the implementation of Islamic leadership in realizing a religious school culture at Madrasah Aliyah Tahfidz Al Qur'an Al Islami, Pesanggaran, Banyuwangi. Using a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews with the principal, teachers, and students, as well as documentation analysis of religious programs and institutional policies. The data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. Triangulation and credibility checks were employed to ensure data validity. The results of this study indicate that the religious school culture at Madrasah Aliyah Tahfidz Al Qur'an Al Islami is strongly shaped through worship habit programs, the principle of deliberation in leadership, and the internalization of Qur'anic values in the curriculum and daily activities. Theoretically, these findings reinforce organizational culture theory and transformational leadership theory, which emphasize the importance of consistency in values, role modeling, and collective participation in shaping individual character. This study also affirms the concept of hidden curriculum and continuous spiritual values-based character education.